PENGARUH SOLVABILITAS, PROFITABILITAS, UKURAN PERUSAHAAN, AUDIT TENURE DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG - Muhammad Daffa Dewanto; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of solvency, profitability, firm size, audit tenure, and KAP reputation on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2021.            This research used manufacturing companies during the 2020-2021 with a total sample of 327 samples. Sampling based on a purposive sampling method that follows certain criteria(s). The analytical method used in this research is multiple linear regression analysis.            The results of this study show that solvency has a positive and significant impact on the audit report lag. Profitability and firm size have a significant negative effect on audit report lag. Meanwhile, the effect of audit tenure and KAP reputation are not significant on the audit report lag.